Traffic information collecting algorithms for road selection decision support in vehicle ad hoc networks. (1st January 2012) - Li, Demin; Li, Qiuran; Wang, Jiacun
Traffic information collection is critical issue for vehicle drivers. How to gather the traffic information is a challenge problem. We know that the more the traffic density is, the faster the data delivery is in a vehicle ad hoc network. We also know that the more traffic density is, the more traffic jam probability maybe. So the traffic density is a double edged sword. We may use the road with dense traffic density to transmit road information while use the road with thin traffic density to drive. This paper provides novel ideas to identify traffic density, traffic flow and to support road selection in vehicle ad hoc networks. Using the hop counter, speed detector in packet header, we give traffic density, traffic flow detection algorithm. Consider real time decision of road selection, road dynamic selection algorithm is presented by packet delay. Consider there may be no path to select, all the paths are jammed, carry-and-forward scheme maybe a robust transmit mode in disconnected and delay network, we present a carry-and-forward method to collect road information and predict the road situation in the end.